Ovarian stimulation in IVF couples with severe male factor infertility: GnRH antagonist versus long GnRH agonist - Lv, Mu; Yu, Juanjuan; Chen, Peiqin; Xiao, Qimeng; Lou, Liqun; Luo, Yifan; Yuan, Mu; Xu, Yuan; Feng, Youji; Bai, Mingzhu; Zhang, Zhenbo; Li, Linxia (Frontiers in Endocrinology, 2022)
Objective: To examine the efficacy of gonadotropin releasing hormone (GnRH) antagonist (GnRH-ant) protocol and the long GnRH agonist (GnRH-a) protocol during in vitro fertilization (IVF) therapy in patients with severe male infertile factors. Methods: A total of 983 women with severe male factor infertility undergoing IVF therapy from 2017 to 2020 at one center were retrospectively analyzed. Patients were divided into the GnRH-ant group (n=527) and the GnRH-a group (n=456) according to their ovarian stimulation protocols. Patient baseline characteristics, ovarian stimulation characteristics, and clinical pregnancy outcomes were compared between the groups. The live birth rate was considered the main pregnancy outcome. Results: GnRH-a group had a higher live birth rate compared with the GnRH-ant group (41.0% versus 31.3%, p=0.002). Moreover, the implantation (32.8% vs. 28.1%, p=0.033), biochemical pregnancy (52.4% versus 44.8%, p=0.017), clinical pregnancy (49.3% versus 39.7%, p=0.002) and ongoing pregnancy rates (43.2% vs. 34.9%, p=0.008) were higher in GnRH-a group. For patients with one embryo transferred, the GnRH-a group demonstrated higher live birth (37.0% vs. 19.4%, p=0.010) and ongoing pregnancy rate (38.9% vs. 24.5%, p=0.046) than the GnRH-ant group. Among patients with two embryos transferred, the live birth rate was also higher in the GnRH-a group than in the GnRH-ant group, with no statistical difference. No significant differences were observed in the biochemical abortion rate, clinical miscarriage rate, early miscarriage rate, late miscarriage rate, heterotopic pregnancy rate, twin pregnancy rate, and birth sex ratio between the two groups. Conclusion: For individuals with severe male infertility undergoing IVF, the GnRH-a protocol is considered a more efficient and feasible strategy with a higher live birth rate compared to the GnRH-ant protocol, especially in single embryo transfer.